Innovative Seizure of Metal/Metal Oxide Nanoparticles in Water Purification: A Critical Review of Potential Risks. (2nd November 2019) - Din, Muhammad Imran; Nabi, Amna Ghulam; Hussain, Zaib; Arshad, Muhammad; Intisar, Azeem; Sharif, Ahsan; Ahmed, Ejaz; Mehmood, Hafiz Arslan; Mirza, Muhammad Latif
Abstract: Water contamination is a worldwide critical issue for the present society to avoid competition and maintain an environmentally friendly scenario. Removal of various pollutants including inorganic and organic compounds from water is a big challenge nowadays. Worldwide attention to promote polluted water and technologies related to its treatment has been adversely increased. The utilization of metal/metal oxide nanoparticles (NPs) for this purpose has gained much attention due to its exceptional properties imparted by reduced size and effective surface area. Moreover, metal/metal oxide NPs-based innovation for improved expulsion productivity is an ingenious area for research and development but the use of such NPs presents some serious risks. Herein, the advanced requisition of NPs for polluted water treatment is highlighted along with the difficulties related to them and their toxic impacts when used as water purifiers. Additionally, the plausible fate of metal/metal oxide NPs incorporated in the water for purification and salient future challenges are deliberated.